Analysis of the Achievement of Minimum Service Standards for Mental Health Services in Surabaya - Restuningati, Ririn; Hargono, Arief; Qurniyawati, Eny; Christanto, Daniel (Universitas Airlangga, 2025)
Background: Indonesia is facing a mental health crisis, with 1 in 10 people experiencing mental disorders. Among the 282,654 households with individuals suffering from severe mental disorders, only 0.6% are receiving treatment, and just 0.5% are regularly taking medication. In Surabaya, 0.19% of the population is identified as People with Mental Disorders (PMD). Objective: This study aims to evaluate the achievement of the Minimum Service Standards (MSS) Policy for Mental Health on PMD in Surabaya in 2023. Methods: This research utilized a cross-sectional design and descriptive analysis to analyze data. Secondary data was gathered from a cohort of PMD services within the Surabaya Health Service Working Area in 2023, involving a total sample of 5,766 PMD individuals. Results: In 2023, the MSS for People with Mental Disorders achieved 100.3%, surpassing previous years and meeting the target of 100%. However, that achievement was not consistent across all health centers in Surabaya. About 48% of community health centres did not meet the MSS target. This shortfall is attributed to the presence of specialized social institutions for mental health cases and the absence of mental health post activities in certain areas. Conclusion: The implementation of the Mental Health MSS for PMD in Surabaya in 2023 met the Ministry of Health's target, achieving 103.33%. The trend from 2020 to 2023 shows a continuous increase in MSS implementation, though the distribution of achievements is uneven across community health centers. Out of 63 health centers, 30 (48%) have not yet reached the 2023 MSS.